Secure Pesticide Storage: Using and Managing a Pesticide Storage Facility - Thomas W. Dean (EDIS)
This document identifies and describes six practices that together form a use and management plan for a pesticide storage facility. This document is Fact Sheet PI-33, part of a series from the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004. Revised: November 2004.